An analysis of staff accounts of working with women with personality disorder diagnoses - O'Key, Victoria (2014)
The personality disorder (PD) concept has attracted widespread criticism (see Cromby, Harper & Reavey, 2012). Research suggests those who receive this diagnosis are often stigmatised by mental health professionals. Psychological approaches to understanding staff views about PD have been dominated by realist methodologies which are limited in their capacity to attend to the complexity, contradictions and context of health professionals’ views. Recently, studies have explored the ways that mental health staff talk about their work and account for their treatment decisions; these studies show how dominant categories and practices are produced and maintained through staff talk (see Harper, 1995; Parker, Georgaca, Harper, McLaughlin, & Stowell-Smith, 1995). A central aim of this thesis is to contribute to the body of research which has explored staff discursive practices, their function and their relationship with wider discourses. This study set out to explore the PD construct and how staff make sense of distress within this diagnostic framework. This research is informed by a social constructionist perspective. Semi-structured interviews were used to elicit talk regarding PD, diagnosis and what staff constitute as key elements of their work. Staff were recruited from across a multidisciplinary (MDT) team; all participants (n = 11) worked in a secure, inpatient PD ward in an independent hospital. The analysis was informed by discursive psychology (Potter & Wetherell, 1987) and Foucauldian discourse analysis (Foucault, 1979). Staff both drew on and resisted the practice of diagnosis. Staff foregrounded a biopsychosocial framework for understanding PD and variably questioned the status of PD as a mental illness. Staff talk about the challenges and goals of their work centred on constructions of emotion and emotional control. Implications are discussed in terms of staff decisions about care, the role of clinical psychologists within MDT’s and the wider socio-political context around PD. The current findings draw attention to the construction of psychological concepts in understanding PD, and the essentialist treatment of diagnosis, as well as the complexity and flexibility of implementation of these strategies to justify decisions. There is a need to foster space to explore staff values, mainstream categories and to reflect on dominant ideologies which will influence staff work with people with a PD diagnosis.